PREPARAÇÃO DE COMPOSTOS ORGÂNICOS COM POTENCIAL APLICAÇÃO EM DISPOSITIVOS FOTOVOLTAICOS: AVALIAÇÃO DE PROPRIEDADES FOTO-FÍSICAS E ELETROQUÍMICAS - Klider, Karine Cristina Carrilho Weber dos Santos (2016)
In this study, we evaluated the optical and electrochemical properties of organic compounds of different types in order to analyze their potential for application active layer in photovoltaic devices. The work was divided into three parts. The first discloses the preparation and characterization of a derivative of 1,8-naphthalimide chromophore prepared from the reaction with a benzonitrile unit (also synthesized and characterized in this work). The BID-NB compound showed optical and electrochemical properties equivalent of the chromophore with optical and electrochemical band gap of 3.41 eV and 2.19 eV. Photovoltaic devices using bilayer architecture, constructed with the compound as the active layer, reached 0.9% of power conversion efficiency (PCE) and a current density at short circuit of 5.68 mA cm-2 by using the C70 fullerene as electron acceptor layer, and 1,8-diiodoocthane as additive in the solution for active layer deposition. The second part the work described the preparation of conjugated molecules (with electron donor acceptor characteristics) from the indigo dye modification by addiction of thiophene units. It was found that increasing number of thiophene units resulted in better opto-electrochemical properties. The molecule that showed the best behavior, DHT-IND, presented optical and electrochemical band gap of 1.64 and 1.45 eV respectively. Despite the low band gap value, the bulk heterojunction (BHJ) solar cell constructed with a 1: 3 mixture of DHT-IND and PC71BM as active layer, showed PCE of 0.7% and current density at short circuit of -4.59 mA cm-2. The fill factor (FF) was 26%. In the third part of this work we evaluated the photocurrent generation by the copolymer PPV/DCN-PPV formed by DCN-PPV chains attached to PPV chain. The evaluation performed as film deposited on a glass substrate containing ITO coated, which has exposed to a LED ilumination. After irradiation the copolymer generated current of A cm-2 (unstable), and -2 A cm-2 (stable).